2019
DOI: 10.1002/jhet.3452
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Docking Studies of Some 1,2,3‐Benzotriazine‐4‐one Derivatives as Potential Anticancer Agents

Abstract: Newly synthesized 1,2,3‐benzotriazine‐4‐one derivatives substituted at position‐3 were characterized by various analytical and spectral techniques. The in vitro antitumor activity was evaluated against three different cell lines (liver cells cancer, colorectal cancer, and breast cancer), where compounds 7b, 15, and 25 showed strong antitumor activity with IC50 ranging from 5.54 to 16.26 μM. In addition, molecular modeling studies using MOE were performed to investigate their binding modes to the C‐Met kinase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…(iv) The interactions appeared to covering all possible types, such as π-H, π-π, H-donor and H-acceptor. (v) From all the previous remarks the best inhibition may be expected for 17a , 24 and 19f against the 1ydo protein of Bacillis subtilis bacteria [34,35]. The displayed images of docking complexes (Figure 5 and Figure S3), especially with the interacting image (A), clarify the formerly concluded data.…”
Section: Resultssupporting
confidence: 61%
“…(iv) The interactions appeared to covering all possible types, such as π-H, π-π, H-donor and H-acceptor. (v) From all the previous remarks the best inhibition may be expected for 17a , 24 and 19f against the 1ydo protein of Bacillis subtilis bacteria [34,35]. The displayed images of docking complexes (Figure 5 and Figure S3), especially with the interacting image (A), clarify the formerly concluded data.…”
Section: Resultssupporting
confidence: 61%
“…So, designing new synthesizes play therapeutic role against 4irk and 4cyf, needs preliminary test through this docking module. Each docking process was the average of 30 trails, [43] which translated to significant data (Table 8), interacting patterns and surface-maps ( Figure 9 and S8, S9). With respect to extracted data, we gathered the following notices; i) the interacting ligand-centers were, complexes, played superior inhibition activity towards two selected proteins in comparing to free derivatives, especially with inflammation enzyme.…”
Section: Moe-docking Studymentioning
confidence: 99%
“…39 In vitro antitumor activity of the domino products 20h was evaluated against three different cell lines but low activities were observed compared to other non-related products synthesized in the same publication (entry 8, Table 2). 40 Another research group has synthesized 2-pyridones 20i bearing an antipyrine (known for its anti-inflammatory and analgesic properties) moiety (entry 9, Table 2) 41 and 2-pyridones incorporating a sulfonamide group (entry 10, Table 2) and it was shown that the domino product 20j (R = MeO) exhibited a…”
Section: Scheme 4 Synthesis Of Spiropiperidinediones 6e and Aromatase Inhibitor Pyridoglutethimide 6fmentioning
confidence: 99%
“…39 The in vitro antitumor activities of the domino products 20h were evaluated against three different cell lines, but low activities were observed compared to other non-related products synthesized in the same publication (Table 2, entry 8). 40 Another research group has synthesized 2-pyridones 20i bearing an antipyrine moiety (known for its anti-inflammatory and analgesic properties) (Table 2, entry 9) 41 and 2-pyridones incorporating a sulfonamide group (Table 2, entry 10); it was shown that the domino product 20j (R = MeO) exhibited a significant anticonvulsive effect. 42 It was also demonstrated that some of the domino products 20k displayed moderate to good antimicrobial activity (Table 2, entry 11).…”
Section: Review Synthesismentioning
confidence: 99%